(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article examines the two main types of modality in Arabic: objective and subjective modality. Objective modality is related to objective events and situations and usually represents objective reality. Subjective modality is related to subjective thoughts, decisions, probabilities, and feelings and reflects the speaker’s point of view. The article analyzes modality in Arabic from the perspective of syntax, semantics, and pragmatics, and also examines the use of objective and subjective modality and their problems in translation. This analysis helps to gain a deeper understanding of the syntactic and semantic features of the Arabic language.